Validation of transbronchial cryobiopsy in interstitial lung disease - interim analysis of a prospective trial and critical review of the literature - Hagmeyer, Lars; Theegarten, Dirk; Treml, Marcel; Priegnitz, Christina; Randerath, Winfried (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Transbronchial Cryobiopsy (Cryo-TBB) represents a new approach for sampling lung tissue in interstitial lung disease (ILD). Objectives: Comparing the reliability of Cryo-TBB results and the procedure’s complication rates with the procedure of surgical lung biopsy (SLB). Methods ILD subjects with the need of lung tissue sampling are analyzed in this prospective trial. To determine the relevance of procedure-related complications the pooled data from the ongoing and previous Cryo-TBB studies were compared with pooled data from previous SLB studies in an interim analysis. In our own cohort we analyzed how often Cryo-TBB results lead to a definite diagnosis without the need for a SLB. In subjects who underwent both procedures it was determined how often SLB confirmed Cryo-TBB findings. Results Analyzing the pooled data of the ongoing study (19 subjects) and our own retrospective study (32 subjects), in 38/51 subjects (75%) SLB was deemed to be unnecessary following Cryo-TBB. In 12/13 subjects an SLB was performed confirming Cryo-TBB results in 92%. 30 day-mortality was 1.9%, bleeding occurred in 78%, pneumothorax in 22%. 2 subjects showed a myocardial infarction. Complication rates are comparable to previous Cryo-TBB studies. Analysis of the pooled data from the literature showed an overall 30-day mortality of 0.7% for Cryo-TBB and 3.3% for SLB. Conclusions Cryo-TBB may be a reliable diagnostic tool in ILD, dispensing the need for a SLB in most cases. Severe complications may occur less frequently than in SLB. Modifications of the procedure may lead to further risk reduction.